Design of Unambiguous Combined Tracking Loop for GNSS Complex Subcarrier Signal (Xibei Gongye Daxue Xuebao, 2018)
Complex subcarrier modulation signal, is a kind of BOC signal which is used complex exponential function as subcarrier, has been widely applied in GNSS(Global Navigation satellite system). The existence of multiple correlation peaks of the autocorrelation function of the complex subcarrier signal, will cause the acquisition error and tracking to the side peak when the signal is synchronized. To solve this problem, an unambiguous combined tracking loop for complex subcarrier signals is proposed. In this loop architecture, the main loop completes the coarse synchronization with BPSK-like algorithm, and the assisted loop realizes the accurate tracking together main loop. In this paper, the dual estimate tracking algorithm and the side-peak cancellation scheme are employed respectively in the assisted loop. The performance of tracking accuracy and anti-multipath capability of the proposed architecture is analyzed, and the practicability is verified by using the actual collected data. Simulation and experimental results show that the tracking structure proposed in this paper is practical and has good performance of anti-noise and anti-multipath.